Osteoporotic vertebral fractures: an update - Daskalakis Ioannis I.; Bastian Johannes D.; Mavrogenis Andreas F.; Tosounidis Theodoros H. (SICOT-J)
Introduction: Osteoporotic vertebral fractures (OVFs) are the most common type of fragility fractures. They have a significant and usually detrimental impact on the patient’s functional status and mortality rate, constituting a substantial burden for the patients, their families, and the healthcare system. This narrative review aims to summarize the current knowledge of osteoporotic vertebral fractures and secondary fracture prevention. Methods: A comprehensive literature search was conducted across major medical databases, including PubMed, Scopus, and Web of Science. Relevant studies, guidelines, and reviews published were analyzed to provide a broad perspective on the topic. Results: Diagnosis of OVFs is based on history, clinical examination, and plain lateral radiographs of the spine. Their management is mainly non-operative, with surgery being reserved for specific indications. Successful management of osteoporotic vertebral fractures entails alleviating pain, early restoration of mobility, and secondary fracture prevention. Prevention of the next osteoporotic fracture is paramount and should be an integral element of their management. The Fracture Liaison Service (FLS) is the main contemporary service that serves this purpose. Discussion: Diagnosis of OVFs is simple but requires vigilance from the clinicians. Early, accurate diagnosis is essential to initiate appropriate treatment and provide the opportunity for secondary fracture prevention.